Trees of the Central Valley of Costa Rica: reproduction. Cedro. - Rojas-Rodríguez, Freddy (2013)
The following issue presents a brief description about the “cedro” tree (Cedrela salvadorensis Stadl.) including information about its phenology which directlyrelates to fruit recollection, seed treatment, nursery, and germination processes.